Bezpośrednie inwestycje zagraniczne w teorii poziomu rozwoju gospodarczego w wybranych państwach świata - Graczyk, Beata (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The aim of this article is to reveal and comment on the results of a test checking the relations between the nett value of the foreign direct investment FDI and the gross domestic product per capita, this connection is the subject of Dunning’s theory of economic development. The test was conducted on the basis of data from selected countries in order to compare correlation tendencies in various regions of the world.The analysis of the interrelationship between both phenomena revealed that in four out of thirteen selected countries a statistically significant positive correlation appeared, only Hungary had a negative correlation. Statistical hypothesis test on the lack of correlation was rejected solely for five countries with high Pearson product–moment correlation coefficient, which allows one to state with 95% probability that such relation occurs in randomly chosen time series. The correlation coefficient assumed the highest value of 0.7. It allows one to claim that the theory of economic development does not fully account for the appearance of the foreign direct investment. This phenomenon is influenced by various micro- and macroeconomical factors which facilitate the decision to transfer the capital to other countries’ economies.
Keywords: inwestycje zagraniczne; rozwój gospodarczy; bezpośrednie inwestycje zagraniczne